A Survey on Comparative Study of Customer Behaviour in Online and Offline Purchase of Electronic Items in Ahmedabad - Khan, Arbaz; Makwana, Anjali; Vidani, Jignesh (International Journal of Economics, Business Management and Accounting (IJEBMA), 2023)
Online shopping is quite a new thing these days, although some people are still unaware of it. Although everyone uses the word "shopping" regularly, Internet shopping is becoming more and more popular these days. When everyone goes to shopping, some people get what they need, while others buy more. It means that it can satisfy an internal objective. If someone wants to talk to a close friend or relative, they can send them messages without any charges, search anything on Google, locate someone, express their love towards them through gifts, etc. This is an advantage of modern technology. This study examines consumers who purchase electronic goods online or offline. Even though traditional markets are shrinking due to the expansion of the Internet, some customers still prefer to shop offline. Since it is difficult to buy electronic products online, most people decide to buy offline, while some people prefer to buy online. The overall study aims to determine the percentage of consumers who prefer to purchase electronic items through both offline and online mediums.The research analyses what customers' preferences, decision-making processes and behavior vary between online and offline shopping scenarios. Through the analysis of the relationship between traditional offline merchants and online shopping, this study seeks to identify consumer decision-making variables in the complex market of Ahmedabad